Implementing Adaptive Applied Behavior Analysis to Improve Functional Communication in Inclusive Early Childhood Education - Nuligar Hatiningsih; Childa Kumala Azzahri; Wening Rahayu (Yayasan Darussalam Bengkulu, 2026)
This study aims to examine the implementation of adaptive Applied Behavior Analysis (ABA) in an inclusive Early Childhood Education (ECE) classroom and to analyze its contribution to improving functional communication skills of a child with special needs. The research employed a Single Subject Research (SSR) approach using an A–B design consisting of baseline and intervention phases. The participant was selected through purposive sampling based on identified functional communication difficulties and parental consent. Data were collected through systematic observation using a structured observation sheet to record the frequency of functional communication behaviors across sessions. The operational indicators included the child’s ability to express needs, respond to instructions, initiate interaction, and express acceptance or refusal. Field notes and classroom documentation were used as supporting qualitative data. Instrument validity was established through expert judgment to ensure content relevance to functional communication constructs. Data were analyzed using visual analysis procedures in SSR, focusing on changes in behavioral level, trend direction, and data stability across phases. In addition, Percentage of Non-Overlapping Data (PND) and Tau-U were calculated to estimate effect size. The findings revealed a significant increase in functional communication frequency during the intervention phase, reflected in an upward trend, improved stability, PND of 100%, and Tau-U of .95, indicating a strong intervention effect. The results suggest that adaptive ABA strategies, when integrated into natural classroom routines, effectively enhance functional communication and reduce maladaptive behaviors in inclusive early childhood settings. This study contributes theoretically by recontextualizing ABA principles within inclusive pedagogy and practically by offering a flexible, evidence-based intervention model for early childhood educators.